Computer-assisted pronunciation training: From pronunciation scoring towards spoken language learning - Chen, Nancy F.; Haizhou Li (2016 Asia-Pacific Signal and Information Processing Association Annual Summit and Conference (APSIPA), 2016)
This paper reviews the research approaches used in computer-assisted pronunciation training (CAPT), addresses the existing challenges, and discusses emerging trends and opportunities. To complement existing work, our analysis places more emphasis on pronunciation teaching and learning (as opposed to pronunciation assessment), prosodic error detection (as opposed to phonetic error detection), and research work from the past five years given the recent rapid development in spoken language technology.